The Application of Basic Accounting to Improve the Financial Performance of Toko Asia Baru - Nastasya Cindy Hidajat (Advances in Community Services Research, 2026)
Purpose: This community service activity aims to improve Toko Asia Baru’s financial management capabilities through the application of basic accounting principles. The challenges faced by the partner include unsystematic recording of transactions, a lack of separation between personal and business finances, and the absence of a simple profit-and-loss statement. Method: The activity will be held in April 2026 at Toko Asia Baru and is aimed at business owners. The methods used will include observation, interviews, development of a simple bookkeeping format, basic accounting training, assistance with recording transactions, preparation of a simple profit-and-loss statement, and evaluation of the activity. Results and Discussion: Before the intervention, the partner had not maintained consistent financial records and lacked a profit-and-loss statement. After the intervention, the partner established a simple bookkeeping system, distinguished between cash inflows and outflows, and began preparing a simple profit and loss statement as a basis for evaluating the business. Implications: This activity enhances partners’ knowledge, skills, and awareness regarding business financial management. Ongoing support is needed to ensure the sustainability of financial record-keeping practices.